The Influence of Perceived Social Support on Burnout Mediated by Emotional Regulation in Hasanuddin University Co-Assistant Students - A, Asrini; Tetteng, Basti; Kusuma, Perdana (Polteknik Ilmu Pemasyarakatan, 2025)
Burnout experienced by co-ass school students can affect their concentration, thus affecting the services provided to patients. Burnout can be overcome by increasing perceptions of social support and emotional regulation. This research aims to examine the influence of perceived social support on burnout through emotional regulation which acts as a mediating variable. This research uses quantitative methods. The subjects in this research were co-ass school students at Hasanuddin University with a population of 350 subjects, and there were 185 respondents who participated in this research. The results showed that emotional regulation had a role as a mediator on the influence of perceived social support on burnout (B = -0.156, p = 0.009), with a contribution of 30.2%. Based on the research results, it also shows that perceived social support has a negative and significant effect on burnout. On the other hand, perceived social support also has a positive and significant impact on the emotional regulation abilities of co-ass g school students. Apart from that, emotional regulation abilities have also been proven to have a negative and significant impact on burnout levels. The implications are expected to provide positive contributions, especially in the field of Psychology and also for medical schools that emphasize the importance of paying attention to perceptions of social support and emotional regulation in interns to reduce burnout levels. In addition, this study can also be an additional important reference related to the topic of burnout, perception of social support and emotional regulation.